Teaching Journalists About Violence Against Women Best Reportage Practices: An Australian Case Study. (26th November 2022) - Easteal AM, Patricia; Blatchford, Annie; Holland, Kate; Sutherland, Georgina
ABSTRACT: Media reporting of violence against women (VAW) has the potential to contribute to improving the community's understanding and response to this social problem. However, journalists are not immune to gender biases and myths concerning VAW. Both can affect how the subject is framed. We look at an Australian training programme implemented to improve VAW news reporting practices such as including social context, family violence experts and help-seeking information for survivors, challenging myths and avoiding perpetrator exoneration and victim-blaming. We compare journalists' reporting before and after training and also compare the trained reporters' content with a matched comparison sample written by untrained journalists to see if training translates into best practice reporting. We conclude that reportage practices have improved overall in recent years and that the training model, in which participants were selected to take part, appears to be effective in improving some key elements of best practice reporting, but some areas of concern remain. We recommend more targeted programmes with curriculum additions to better address some reporting deficiencies we identify.